2018
DOI: 10.1002/jlb.2mir0917-354r
|View full text |Cite
|
Sign up to set email alerts
|

New revelations from an old receptor: Immunoregulatory functions of the inhibitory Fc gamma receptor, FcγRIIB (CD32B)

Abstract: The Fc gamma receptor IIB (FcγRIIB/CD32B) was generated million years ago during evolution. It is the sole inhibitory receptor for IgG, and has long been associated with the regulation of humoral immunity and innate immune homeostasis. However, new and surprising functions of FcγRIIB are emerging. In particular, FcγRIIB has been shown to perform unexpected activatory roles in both immune-signaling and monoclonal antibody (mAb) immunotherapy. Furthermore, although ITIM signaling is an integral part of FcγRIIB r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 109 publications
0
25
0
1
Order By: Relevance
“…The anti-mouse PD-1 clone RMP1-14, utilized for the treatment of tumor-bearing athymic mice, is a rat immunoglobulin IgG2a reported to interact with the mouse inhibitory receptor, FcgRIIb (13). FcgRIIb has been shown to be involved in dampening the immune response, and impairments in FcgRIIb function are associated with an exacerbation of inflammatory processes (29). The anti-human PD-1 antibody nivolumab is an IgG4 isotype with reduced binding affinity to activating FcgRs, thereby avoiding antibody-dependent cell-mediated cytotoxicity on PD-1 þ immune cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-mouse PD-1 clone RMP1-14, utilized for the treatment of tumor-bearing athymic mice, is a rat immunoglobulin IgG2a reported to interact with the mouse inhibitory receptor, FcgRIIb (13). FcgRIIb has been shown to be involved in dampening the immune response, and impairments in FcgRIIb function are associated with an exacerbation of inflammatory processes (29). The anti-human PD-1 antibody nivolumab is an IgG4 isotype with reduced binding affinity to activating FcgRs, thereby avoiding antibody-dependent cell-mediated cytotoxicity on PD-1 þ immune cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, CD32B is expressed and inducible by IL-4 on human monocytes and can inhibit CD32A-mediated macrophage activation. 20,21 Furthermore, it was shown that coexpression of CD32A and CD32B on monocyte-derived DCs reveals a homeostatic checkpoint for inducing tolerance or immunity by immune complexes (ICs). 22 These studies suggest that CD32 might be crucial in modulating the allergic immune responses in asthma via regulating monocytes activities.…”
Section: Introductionmentioning
confidence: 99%
“…Direct signaling by CD32 is mediated by immunoreceptor tyrosine-based activation motif (ITAM/CD32A and CD32C) (17) and by immunoreceptor tyrosine-based inhibitory motif (ITIM/CD32B) (18). These motifs determine whether the receptors are activating or inhibitory.…”
Section: Fc-receptor Functioning In the Innate Immune Responsementioning
confidence: 99%